Dissociating and linking divergent effects of emotion on cognition: insights from current research and emerging directions - Dolcos, Florin; Denkova, Ekaterina; Iordan, Alexandru D.; Shafer, Andrea T.; Fernández, Guillén; Dolcos, Sanda (Frontiers in Psychology, 2025)
This century has witnessed unprecedented increasing interest in the investigation of emotion-cognition interactions and the associated neural mechanisms. The present review emphasizes the need to consider the various factors that can influence enhancing and impairing effects of emotion on cognition, in studies of both healthy and clinical groups. First, we discuss advances in understanding the circumstances in which emotion enhances or impairs cognition at different levels, both within the same processes (e.g., perception, episodic memory) and across different processes (i.e., episodic vs. working memory). Then, we discuss evidence regarding these opposing effects of emotion in a larger context, of the response to stressors, and linked to the role of individual differences (personality, genetic) affecting stress sensitivity. Finally, we also discuss evidence linking these opposing effects of emotion in a clinical group (PTSD), where they are both deleterious, and based on comparisons across groups with opposing affective biases: healthy aging (positive bias) vs. depression (negative bias). These issues have relevance for understanding mechanisms of emotion-cognition interactions in healthy functioning and in psychopathology, which can inspire training interventions to increase resilience and well-being.